Pelestarian Seni Tradisional Randai dalam Arus Globalisasi: Refleksi Pengalaman Pengabdian Masyarakat di Kenagarian Padang Laweh Malalo, Tanah Datar - Syamsir Syamsir; Jumiati Jumiati; Nora Eka Putri; Ideal Putra (Journal of Education on Social Science (JESS), 2023)
This article was a reflection from experiences of Community Service program among younger generation in Padang Laweh Malalo Village at Tanah Datar Regency. This program was intended to increase the understanding, awareness, and skills the younger generation to the importance of preserving the traditional arts of randai as one of the cultural heritages and at the same time the potential and tourist attraction that has been neglected all this time. This program was inspired by various conditions that indicated the lack of interest, awareness, and skills of the younger generation in preserving this randai art, while on the other hand traditional randai art could be used as an attraction and is a potential for cultural tourism that can be packaged and adapted to the current context. On the other side, the preservation of traditional art like Randai in the face of massive globalization required a comprehensive and multi-faceted approach. This approach included efforts such as documentation, education, partnerships, adaptation, youth engagement, and policy development. Based on this phenomena, various coaching, training and management programs had been done to improve the abilities and skills of the partner groups, especially the youth group who were members of the "Sanggar Seni Salapan Suku" group at Kenagarian Padang Laweh Malalo Tanah Datar, both in terms of knowledge and skills, in order to increase the professionalism of youth groups and it is hope that they could become pioneers and motivators for other youth generations in the development of traditional randai arts.